S33 Physical activity intervention versus pulmonary rehabilitation in copd: the lively copd project. (15th November 2016) - O'Neill, B; O'Shea, OM; McDonough, SM; McGarvey, L; Bradbury, I; Arden, MA; Troosters, T; Cosgrove, D; McManus, T; McDonnell, TJ; Bradley, JM
Abstract : Introduction and objectives: The format of pulmonary rehabilitation (PR) may not meet the needs of all patients with COPD or lead to improved physical activity (PA) levels. Drop outs from PR can be high. A pedometer driven physical activity intervention (PAI) may offer patients an alternative method for increasing their PA. The aim of this study was to assess the feasibility of a 12 week clinician facilitated PAI versus PR in people with COPD. Methods: The design was a multicenter-randomised, parallel-group, feasibility study. Patients with COPD referred for PR were included. Spirometry and demographics were recorded. The following were assessed at baseline, post-intervention and follow up (12 weeks): PA using an ActiGraph GT3X+ accelerometer, sealed Yamax Digiwalker pedometer and the International Physical Activity Questionnaire (IPAQ) (long form); exercise capacity (Incremental Shuttle Walk Test (ISWT)); COPD Assessment Test (CAT). Recruitment, retention and completion/rates were recorded. Descriptive statistics and mean differences were used to analyse the data. Results: 50 patients (mean (SD) age 64 (8) years, 24M, FEV1 1.44 (0.63)) were recruited and randomised: PR n = 26, PAI n = 24. Of those screened 50/651, 13% were recruited. One participant randomised to the PAI started PR, a per protocol analysis was conducted; PR n = 27 and PAI n = 23. Completion of the PAI was 74% (17/23) and PR was 48% (13/27). Retention overall was 74% post-intervention (n = 18 PAI; n = 19 PR), and 66% at follow up (n = 15 PAI; n = 18 PR). There was a mean (95% confidence interval (CI)) change of 972 (−1080 to 3024) steps/day and 4 (−441 to 449) in the PAI and PR group respectively; results are found in Table 1 . There were 4 minor adverse events (PAI n = 3 PR n = 1). Conclusions: This study will inform a future large scale randomised control trial (RCT). The LIVELY PAI intervention appears to be feasible and safe within this preliminary study, and enhanced physical activity in people with COPD. While the results require confirmation in a fully powered RCT, the mean increase in step count is in line with a recently published minimally clinically important difference. 1 Reference: Demeyer H, et al . The Minimal Important Difference in Physical Activity in Patients with COPD. PLoS One . 2016;11 :0154587.